Valgus Knee Angle during Drop Landing in Female and Male Physical Education Major Undergraduate Students : 性別與膝外翻角度及股二頭肌活動之間的關係 - SAM, Ka lam (Asian Journal of Physical Education & Recreation, 2010)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Gender differences in lower extremity landing mechanics and muscle activation have been identified as potential causative factors leading to the increased incidence of anterior cruciate ligament (ACL) injuries in female athletes. Valgus knee alignment places greater strain on the anterior cruciate ligament than a more neutral alignment. Biceps Femoris (BF) may provide dynamic stability to the knee joint during landing, decreasing knee valgus and preventing placing strain on the anterior cruciate ligament. The purpose of this study was to determine if frontal-plane knee angle and Biceps Femoris (BF) activation differ between the sexes at initial contact (IC) and maximal knee flexion (MKF) during a drop landing. Nine male and eight female healthy subjects volunteered to participate in this study. Frontal-plane knee angle and BF average root mean square (aRMS) amplitude were measured using BTS (Bioengineering Technology & Systems) electromyography, video acquisition system and Kistler force platform. It was found that at initial contact, women landed in valgus, and men landed in varus (P < .001). At maximal knee flexion, men reached a greater varus position than women (P < .001). Women’s BF aRMS amplitude was less than men. At initial contact, BF aRMS amplitude significantly differed between groups (P < .05). However, no significance difference between groups at maximal knee flexion (P > .05). To conclude, women tended to land in more knee valgus than men. At initial contact, women performed different and less BF muscle activation than men. The stabilization mechanism in landing knee motion between initial contact and maximal knee flexion is still unknown. 股二頭肌能通過減輕膝外翻程度來增加著地時膝關節的穩定性，從而減輕前十字韌帶受到的張力。有研究表明，不同群體之間下肢著地技術和肌肉活動情況的差異是增加女子運動員前十字韌帶受傷幾率的兩大潛在因素。當膝外翻時，十字韌帶受到比膝蓋處於中立位時更大的張力。本研究通過運用Kistler測力台，肌電圖，以及BTS視頻採集系統對17名(男=9，女=8)主修體育的本科生進行測量，目的在於討論著地瞬間膝關節的角度和股二頭肌活動是否存在性別差異，以及測定著地緩衝後的最大膝角和股二頭肌活動是否存在性別差異。結果發現，在著地瞬間，女性較男性更容易出現膝外翻現象(p<.001)。肌電圖顯示，女性股二頭肌振幅 比男性要小且男女之間存在顯著性差異(p<.05)，但當緩衝至最大膝角時，男女之間的差異並不顯著(p>.05)。著地過程中，下肢肌肉的穩定機制與膝部運動的關係有待進一步探討。